Kandungan Logam Berat dan Vitamin E pada Testis Tikus Wistar setelah Dipaparkan Air Lindi - Elisa Nurma Riana; Ayda T. Yusuf (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the heavy metal content and vitamin E concentration of male Wistar rat testes exposed to Sarimukti landfill leachate. The research design used was a randomized block design. Rats were divided into four treatments, namely: aquabidestylates, 63% leachate, CdCl2, H2O2. The test substance was administered intraperitoneally for 14 days. Heavy metal concentrations were measured using the Atomic Absorption Spectrometry (AAS) method, while Vitamin E concentrations were measured using HPLC. The results showed that the concentration of heavy metal Zn in testicular tissue exposed to 63% leachate was 0.6 ppm, aquabidestylates was 0.5 ppm, while the other six metals had a concentration of 0 ppm. The measurement results of Vitamin E in the 63% leachate treatment were meager, namely, 1.06 ppm when compared to the aquabidestyl treatment of 7.92 ppm, CdCl2 and H2O2 were 0.53 ppm and 0.85 ppm, respectively. In conclusion, Sarimukti landfill leachate can cause an increase in ROS, which is indicated by a biomarker of decreased Vitamin E concentration in the testes, causing testicular damage. Keywords: Leachate, Heavy Metals, Wistar Rat Testicles, Vitamin E